Effect of Duration and Intensity of Burning on Columns Exposure to Cyclic Fire - shakir, nuha; Ali, Ammar (Anbar Journal of Engineering Science, 2022)
The term "fire safety engineering" refers to the process of applying scientific and engineering principles to the effects of fire in order to lessen the number of deaths and property damage caused by fire. This is done by determining the risks that are involved and providing the most effective method for implementing measures of prevention or protection. The paper showing experimental results of ordinary concrete columns made of  "NSC" subjected to axial load and cyclic firing is presented in this study. the bearing capacity of the column decreased. all samples have been loading an eccentric load with  "e = 75 mm" ,"e / h = 0.50," and the ratio Celsius (30%Pu) continuously through the burning period. The first column(C1) was the sample control with out exposure cyclic fire  , and the second column was subjected to four burning cycles over the course of four days, with a duration specific of "45 minutes" for each cycle, at a temperature of "400 °C", and the third column was subjected to four burning cycles over the course of four days, with a duration longer amount of "75 minutes" for each cycle, at a temperature of "400 °C, ", the four column was subjected to four burning cycles over the course of an  of four days, with a duration specific of "45 minutes" for each cycle, at a temperature of "600 °C " , the bearing capacity of the column decreased. that to be amount losses (C2,C3 and C4) comparison to (C1) equile ( 27.20 , 29.12, and 36.40)% respectively.  the fracture load of the experimental columns varied by decreasing with these variables. Additionally, the depth and spread of the cracks increased with the increase in burning duration and target temperature.